PENGEMBANGAN E-MODUL DENGAN PENDEKATAN DEEP LEARNING DAN ROLE PLAYING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA MATERI NEGOSIASI BISNIS KELAS XI BISNIS DIGITAL (STUDI DI SMKN 2 BUDURAN SIDOARJO) - Ramadhania Sany, Santi; Dwijayati Patrikha, Finisica (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is driven by the lack of interactive and contextual learning experiences in business negotiation lessons due to the continued use of conventional teaching methods, which have resulted in low student activity and learning outcomes. This research aims to identify the stages of developing an e-module based on a deep learning approach and role playing method, assess its feasibility, and analyze student responses to the e-module on their learning activities and outcomes. The research method employed is Research and Development (R&D) with a 4-D development model, limiting the study to the define, design, and develop stages. The research subjects consisted of 36 students. Data collection techniques included observation, questionnaires, and learning outcome tests, with quantitative descriptive data analysis. The results showed that the developed e-module achieved a feasibility level of 91.50%, which falls into the very feasible category. Student responses to the use of the e-module reached 95.83%, categorized as very good. Student learning activity increased from 48.33% to 90.00%. Furthermore, learning outcomes also improved, as shown by the increase in the average pre-test score of 64.81 to an average post-test score of 90.51. Based on these results, the e-module based on a deep learning approach with the role-playing method is declared very feasible for use and shows an improvement in student learning activity and outcomes in business negotiation material.